Data Arbitration in the Digital Economy: The Need for a Specialized Data Dispute Arbitration Forum in Indonesia - Firman Nurdiyansyah Sunandar; Ahmad Juaeni; Johannes Triestanto; Andri Herman Setiawan (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
The rapid expansion of Indonesia’s digital economy and the enactment of the Personal Data Protection Law (Law 27/2022) have exposed significant shortcomings in the resolution of data-related disputes under existing judicial and administrative frameworks. Public adjudication of sensitive data conflicts can erode trust, impose reputational damage, and delay reparative outcomes, while courts often lack specialized expertise in technology and privacy. Drawing upon international precedents including the European Data Protection Board’s Article 65 GDPR mechanism, the EU–US Data Privacy Framework arbitration annex, and the European Patent Office’s data-protection arbitration rules this study examines the urgency and feasibility of establishing a dedicated Data Dispute Arbitration Forum in Indonesia. Through comparative analysis, it identifies core design elements such as expert-appointed tribunals, streamlined online procedures, confidentiality safeguards, clear enforcement under the New York Con-vention, and mechanisms for restorative remedies beyond fines. Anchored in Pancasila’s social-justice ethos and Indonesia’s ADR law (Law 30/1999) and ITE Law, the proposed institutional architecture integrates online dispute resolution (ODR) protocols, data-minimization and cybersecurity guidelines, and publicly anonymized award publication to foster legal certainty and raise awareness of data-protection obligations. A stakeholder impact assessment demonstrates that such a forum would benefit individual data subjects through low-cost, expeditious relief; controllers and processors through predictability and trade-secret protection; regulators through expert findings; and foreign investors through alignment with global data-governance standards. By aligning domestic legal values with international best practices, the specialized forum promises to bolster enforcement, restore public trust, and strengthen Indonesia’s competitiveness in the global digital marketplace.